A simulation-based study on the disc brake temperature distribution for optimising hole geometry. (21st November 2021) - Sharma, Shyam Sunder; Raju, Hariharan; Tomar, Pranay Singh; Jangid, Rajesh; Khatri, Rahul
Disc brakes used in automobiles are responsible for braking to ensure a smooth and safe ride. This study deals with the thermal analysis of a disc brake rotor under various geometry of holes cut on the disc rotor surface. The friction on the disc escapes in the form of heat from the surface of the disc rotor. The temperature observed on the surface of the rotor, because of the friction developed between the brake pads and the rotor is analysed using ANSYS 18.1. The rotor is designed by assuming appropriate parameters in SolidWorks 17. The temperature distribution and total heat flux were observed using ANSYS 18.1. The analysis was carried out on different hole geometries, i.e., circular, square, 3/4th circular, straight slots, and rotor without holes. The dissipation of heat was found better in disc rotor with holes as compared to rotor without holes. The simulation study shows that the slotted holes on the disc rotor have a surface temperature, i.e., 89.356°C which is lower compared to the other four cases. This study concludes that the performance of the brakes can be improved with the help of the holes cut on the disc rotor surface and the best performance can be obtained with slotted holes.